Peran Perempuan dalam Keluarga Petani Pegunungan Tengger - Maria Novita Sitanggang (Umbara, 2018)
Women play double roles in the society, in the public sphere as worker who earn income for the household, and in the domestic sphere as housewives. This research discusses women’s roles in peasant family. This research applies qualitative method. Data collection technique includes participant observation, in-depth interview, and archival study. Data were analysed using AGIL’s theory of social change (Adaptation, Goal, Integration, Latency) by Talcott Parson; and Harvard-Moser gender analytical frameworks. This study suggests that women in peasant family have multiple roles; as a spouse and housewives in domestic sphere, and as farmer and as member of the community in public sphere. Women take responsibility in educating children in the domestic sphere; while in the public sphere, as farmer, they contribute significantly to their family income.